2020
DOI: 10.3390/cancers12071956
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Agent Photodynamic Therapy with Optical Clearing Eradicates Pigmented Melanoma in Preclinical Tumor Models

Abstract: Treatment using light-activated photosensitizers (photodynamic therapy, PDT) has shown limited efficacy in pigmented melanoma, mainly due to the poor penetration of light in this tissue. Here, an optical clearing agent (OCA) was applied topically to a cutaneous melanoma model in mice shortly before PDT to increase the effective treatment depth by reducing the light scattering. This was used together with cellular and vascular-PDT, or a combination of both. The effect on tumor growth was measured by longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The preclinical in vivo experiments described here support the hypothesis that the use of combined cellular and vascular PDT improves therapeutic response compared to single-agent PDT and that optical clearance results in improved tumor response to both single-and dual-agent PDT. The results also indicate the potential of PDT therapy with OCA enhancement in the treatment of pigmented lesions, including melanoma [43].…”
Section: Photothermal Therapymentioning
confidence: 62%
See 1 more Smart Citation
“…The preclinical in vivo experiments described here support the hypothesis that the use of combined cellular and vascular PDT improves therapeutic response compared to single-agent PDT and that optical clearance results in improved tumor response to both single-and dual-agent PDT. The results also indicate the potential of PDT therapy with OCA enhancement in the treatment of pigmented lesions, including melanoma [43].…”
Section: Photothermal Therapymentioning
confidence: 62%
“…Treatment with lightactivated photosensitizers (photodynamic therapy, PDT) has shown limited tumor killing efficacy in pigmented melanoma, mainly due to light scattering and poor light penetration in this tissue [42]. To increase the treatment efficiency by reducing light scattering, an optical clearing agent (OCA) was applied to a mouse model of cutaneous melanoma shortly before the application of single and dual photosensitizer PDT [43].…”
Section: Photothermal Therapymentioning
confidence: 99%
“…The cell growth inhibition was observed due to the irradiation on the cells without PIC treatment (green stars in Figure 5A). As a prospect of this approach in an in vivo study, the doses of irradiation can be increased to maximum energy fluence of 100 J/cm 2 , depending on the selected wavelength, however, visible light irradiation is unlikely to be toxic [42]. Optical microscopic observations before and after PIT demonstrated the bleb formation as signs of necrotic cell death.…”
Section: Photo-cytotoxicity Assaymentioning
confidence: 99%
“…Considering the fundamental restriction of light penetration, we suggest optimizing the excitation of PSs in deep tissue that may give us a highly flexible theranostic platform for HIV researches. This inevitably issue dictates the use of high-power irradiation [42]. The other alternatives for light delivery to the PICs in deep tissue could be the application of cellular-scale inorganic light-emitting diode (µ-ILED) arrays [43], or upconversion nanoparticles (UCNPs) in the field of PIT [44].…”
Section: Confocal Microscopy Studymentioning
confidence: 99%
“…4,[20][21][22][23] In addition, it also has been reported that in vivo skin and skull optical clearing methods can effectively enhance the efficacy of photodynamic therapy. 24,25 Therefore, they have great potentials in clinical application.…”
Section: Introductionmentioning
confidence: 99%